Presidential control of high courts in Latin America: a long-term view (1904-2006) = Control presidencial de las cortes supremas en América Latina: una mirada histórica (1904-2006) - Pérez-Liñán, Aníbal S. (2009)
In many Latin American countries the executive branch manipulatesthe composition of the Supreme Court, and judicial independence hasremained elusive. Because high courts can exercise judicial review and influencelower courts, incoming presidents often force the resignation of adversarialjustices or "pack" the courts with friends. One indicator of this problemhas been the high turnover among members of the high courts. In thispaper we offer systematic evidence to compare this problem across countriesand to place this issue in historical perspective. Our analysis covers 11Latin American countries (Argentina, Brazil, Chile, Colombia, Costa Rica, ElSalvador, Guatemala, Honduras, Mexico, Panama, and Uruguay) between1904 and 2006. We model the entrance of new justices to the SupremeCourt as a function of "natural" (legal and biological) factors, political conditionsempowering the president to reshuffle the Court, and institutionalincentives promoting executive encroachment on the judicia